The no-vertical scar technique for oncoplastic breast reconstruction. (January 2023) - Venardi, Andrew; Newsom, Keeley D.; DeBrock, Will; Pittelkow, Eric; Lester, Mary; Fisher, Carla S.; Ludwig, Kandice K.; Hadad, Ivan; Hassanein, Aladdin H.
Summary: Introduction: Oncoplastic reconstruction can optimize breast conserving therapy. Nipple loss is a concern in patients with significant ptosis and breast hypertrophy particularly with pedicle undermining during tumor resection. The modified Robertson technique (No-Vertical Scar reduction) has been previously described for breast reduction in large, ptotic patients using a wide, bell-shaped inferior pedicle with only inframammary fold and peri‑areolar incisions. The purpose of this study was to evaluate the No-Vertical Scar (NVS) technique applied to oncoplastic reconstruction. Methods: Women undergoing oncoplastic breast reduction using a NVS, Wise, or Vertical method were assessed. Predictive variables included patient demographics, comorbidities, and sternal notch to nipple (SNN) distance. Outcome variables were delayed wound healing, surgical site infection, seroma, fat necrosis, nipple necrosis, use of a free nipple graft, and time between surgery and adjuvant radiation. Results: Fifty patients met inclusion criteria using NVS ( N  = 15), Wise ( N  = 16), and Vertical ( N  = 19) methods. The NVS group had a significantly higher BMI ( p =.009), greater sternal notch to nipple distance ( p =<0.001) and increased resection volume ( p =<0.001) as compared to Wise and Vertical groups. There was no significant difference in complications ( p =.25). No nipple necrosis occurred, and no free nipple grafts were required. Conclusion: The NVS approach is a useful technique for oncoplastic reconstruction in select patients with macromastia and severe Grade II or Grade III ptosis. The wide, bell-shaped pedicle is versatile for obliterating a lumpectomy cavity and optimizing nipple perfusion if pedicle undermining occurs during resection.